Ethnic Variations in Healthcare Service Utilization and Access in Vietnamese Mountainous Setting - Le Anh, Tuan (ScientificWorldJournal, 2021)
Evidence of health service use and access across different target groups is essential for policy development, health promotion, and promotion of equity in healthcare. This study aims to look at ethnic variations in health service use and access among residents in mountainous areas of Vietnam. A cross-sectional descriptive study was conducted on 321 adults from two mountainous communes in Bac Kan province. Healthcare service use and access were evaluated by using a structured questionnaire. Zero-inflated Poisson regression was used to examine the ethnic variations in the healthcare service use and access. Of 321 mountainous residents, 63.6% used health services in the previous 12 months, of which 24.9% respondents used inpatient services and 47.9% used outpatient services. The number of outpatient medical services used by the Tay participant was higher than that of the Kinh and other ethnic groups (p < 0.05). Multivariate regression results showed that compared to Kinh people, Tay people had a higher number of outpatient service use (Coef. = 0.25, p=0.04), while people in other ethnicities had a lower number of service use (Coef. = −0.64, p=0.01). Meanwhile, no difference was found among groups regarding the number of inpatient service use (p > 0.05). This study showed the ethnic differences in outpatient use of health services among communities living in the northern mountainous setting of Vietnam.